Smashing stereotypes: mutual respect, key to embracing diversity - Osier, Faith; Murungi, Linda M. (Trends in parasitology, 2021)
The path to a successful international career in science is daunting for most, and women in Africa are no exception. We are grossly under-represented as senior authors in high-impact publications and keynote speakers at international conferences, and rarely head major funding networks. Smashing long-held stereotypes may ease the journey.
Gesehen am 04.08.2021